(3GdebUO GdCMeO aj GdJYQja HSjOfG GHf YHOGddg CMeOs - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf ef CMSf eGUQa Edjg GdEfSf GgJeGeg eMGSf Cgd Gddg GdhdjGA hEf eef CcQeg Gddg HgPg GdcQGeI SjOi CMeO s
(3BNQgG (B:s
(3Udi Ydjg EdgfG eG CbHdJ HRd JLhH GdadG aGdaQbO s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3Odjd eDQN GdeZQH (B- (3U (B263 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B412 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs